The impact of the national culture on expectations of services: the case of sightseeing in Porto - Oliveira, Fabiana (2019)
The aim of this study is to analyse the impact of the national culture on expectations of services. With the increasing trend of globalization, it is crucial for managers to understand the main cultural differences across the world. If companies want to succeed and create satisfied customers, they must know what each one expects from the service. So, the goal is to determine if customers from different cultures have different expectations on the same service. The empirical case of this study is the international tourist service the Sightseeing, in Porto, Portugal. Five nationalities were selected - French, British, Spanish, German and Brazilian - and a mixed method research was adopted. The results obtained determined that different nationalities mean different expectations. This is useful to international services that want to create satisfied customers.